KARAKTERISASI BAKTERI ASAM LAKTAT (BAL) DARI FERMENTASI TAPE SINGKONG: CHARACTERIZATION OF LACTIC ACID BACTERIA (LAB) FROM FERMENTATION OF CASSAVA TAPE - Erika Nandini; Sylvan Septian Ressandy; Hasyrul Hamzah; Widya Rahmah (Jurnal Penelitian Farmasi Indonesia, 2021)
Indonesia is famous for its wide variety of fermented traditional foods. The type of traditional fermented food that is often found is cassava tape which is made from carbohydrate food using yeast which belongs to the lactic acid bacteria (LAB) group. This study aims to isolate and characterize LAB as probiotics from fermented cassava tape food. The research methods used were the manufacture of sample suspensions, isolation, and purification of microbes, observation of the morphology of the colonies, gram staining of bacterial isolates, acid resistance test, and bile salt resistance test. Based on the results of research from 4 types of samples with different dilutions, macroscopic tests on all samples had irregular colony edge shapes with 3 types of samples of umbonate colony elevation and 1 spreading sample, as well as 2 samples of umbonate colony shape and 2 others spreading. In the microscopic test, all samples belonged to the Gram-positive bacteria group and were rod-shaped. Meanwhile, in the characteristic test of probiotic isolates against pH and bile salts using MRSB medium with two different pH variations, namely pH 2.5 and pH 3, the results showed that there were deposits on the growth of the isolates where the acidity test stated that LAB had met all the test requirements. probiotics. However, in the bile salt resistance test, all isolates grew more optimally on a medium containing 1% ox bile compared to 5% concentration. Therefore, cassava tape can be used as a source of lactic acid bacteria as probiotics.